Effects of a flavonoid-rich juice on inflammation, oxidative stress, and immunity in elite swimmers: A metabolomics-based approach - Knab, A. M.; Nieman, D. C.; Gillitt, N. D.; Shanely, R. A.; Cialdella-Kam, L.; Henson, D. A.; Sha, W. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The effects of a flavonoid-rich fresh fruit and vegetable juice (JUICE) on chronic resting and postexercise inflammation, oxidative stress, immune function, and metabolic profiles (metabolomics analysis, gas-chromatography mass-spectrometry platform) in elite sprint and middle-distance swimmers were studied. In a randomized, crossover design with a 3-wk washout period, swimmers (n = 9) completed 10-d training with or without 16 fl oz of JUICE (230 mg flavonoids) ingested pre- and postworkout. Blood samples were taken presupplementation, post-10-d supplementation, and immediately postexercise, with data analyzed using a 2 × 3 repeated-measures ANOVA. Prestudy blood samples were also acquired from nonathletic controls (n = 7, age- and weight-matched) and revealed higher levels of oxidative stress in the swimmers, no differences in inflammation or immune function, and a distinct separation in global metabolic scores (R2Y [cum] = .971). Swim workouts consisted of high-intensity intervals (1:1, 1:2 swim-to-rest ratio) and induced little inflammation, oxidative stress, or immune changes. A distinct separation in global metabolic scores was found pre- to postexercise (R2Y [cum] = .976), with shifts detected in a small number of metabolites related to substrate utilization. No effect of 10-d JUICE was found on chronic resting levels or postexercise inflammation, oxidative stress, immune function, and shifts in metabolites. In conclusion, sprint and middle-distance swimmers had a slight chronic elevation in oxidative stress compared with nonathletic controls, experienced a low magnitude of postworkout perturbations in the biomarkers included in this study, and received no apparent benefit other than added nutrient intake from ingesting JUICE pre- and postworkout for 10 days.